An Analysis of Flouting Maxim on " Ketua KPK Tersangka Korupsi” Mata Najza Talkshow - Manik, Sondang; Godwill Chenyuei Akwene; Atabong Nee Alemanjoh Maria Nkea; Napitupulu, Eka (Journal of Applied Linguistics, 2024)
This research is aimed at analyzing the flouting of maxims in Mata Najwa's talk show with the topic "Ketua KPK Tersangka Torupsi". The researcher collected data from YouTube video transcriptions as a data source. The data was analyzed using descriptive qualitative ‘The problem is to provide information on the implications of the conversation between the famous Indonesian host and his two guest stars. it is found that material about conversational maxims. The types of maxim flouting found were the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. This research proves the existence of the floating maxim proposed by Grice. It is hoped that the results of this research could become an enrichment and consideration for the development of linguistic research. Keywords: flouting maxim; cooperative principles,